Cumatetralyl as an avicide for use against the Cape sparrow - Heyl, C.W. (South African Journal of Enology and Viticulture, 2017)
The potential of cumatetralyl, an anticoagulant, for controlling the Cape sparrow Passer melanurus (Statius Miiller), and its secondary poisoning hazards to carnivorous vertebrates were investigated under captive conditions. The LD50-value for the Cape sparrow was about 140 times higher than the value reported for the laboratory rat. It is concluded that cumatetralyl is not a suitable agent for use against the Cape sparrow, and that it would constitute a secondary poisoning hazard to predators.